Pemanfaatan Teknologi Pendidikan dalam Meningkatkan Kinerja Guru di Era Digital - Marsha Aulia Ferdinan Putri; Septi Ayu Larasati; Siti Rohayati (Journal on Education, 2025)
This research aims to analyze the use of technology in education, specifically through e-learning and blended learning methods, and their impact on teacher performance. The study employs a qualitative approach, using a literature review to gather and analyze data from various partinent sources. The findings prove that the use of technologies such as e-learning, which facilitates flexible online learning, and blended learning, which combines online and face-to-face learning, significantly contributes to improving teaching quality and learning effectiveness. These technologies help teachers deliver content more effectively, enhance interaction, and create a more engaging and efficient learning experience for students. Therefore, it is crucial to continue supporting teachers' professional development through ongoing training and to ensure the availability of adequate infrastructure to fully leverage the benefits of technology in education. Educational institutions should design appropriate training programs to help teachers adapt to the digital age and enhance teaching quality.